Konstrukcja rei iudicatae decyzji administracyjnej (w Kodeksie postępowania administracyjnego) - Łuczak, Konrad (Kwartalnik Prawa Publicznego, 2012)
This article discusses the doctrine of res judicata in the context of administrative decisions. It explores fundamental issues concerned with this concept, namely that is its essence, basis in legal order, legal character and also its relation to the binding force of administrative decisions.